Policy Safeguards For Countries Seeking Access To Fund Financial Support That Would Lead To High Levels Of Combined GRA-PRGT Exposure. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2020)
This paper proposes safeguards broadly aligned with the GRA exceptional access policy that will apply in cases where combined GRA and PRGT credit exposure exceeds the GRA thresholds. The new safeguards would help to mitigate financial risks to the PRGT and the GRA, respectively, that arise from a member having high levels of combined credit from these two sources of funding. The proposed policy builds on the current policies on safeguards to Fund resources (both the Fund's resources in the GRA and under the PRGT as Trustee, respectively).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet